2018
DOI: 10.3390/plants7010008
|View full text |Cite
|
Sign up to set email alerts
|

Cistus incanus from Strandja Mountain as a Source of Bioactive Antioxidants

Abstract: The purpose of the present study is to survey the extraction conditions and explore the antioxidant potential of the wild herb Cistus incanus, which is non-traditional in Bulgarian ethnomedicine and widespread in the Strandja Mountain. The influence of the extraction time (0–500 min) and solvent composition (0–50% ethanol in water) on the polyphenols, flavonoid yields and on the antioxidant capacity of the extracts of leaves, stalks (wood parts) and bud mixture were studied. The antioxidant capacity (AOC) was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Cistus incanus is called a medicine herbal plant in the Mediterranean due to its antimicrobial, anti-infl ammatory, cytotoxic and antiulcerogenic properties [5,6,31] This work allows the use of the selected infusions with high added value antioxidants to be used such as dietary additives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cistus incanus is called a medicine herbal plant in the Mediterranean due to its antimicrobial, anti-infl ammatory, cytotoxic and antiulcerogenic properties [5,6,31] This work allows the use of the selected infusions with high added value antioxidants to be used such as dietary additives.…”
Section: Discussionmentioning
confidence: 99%
“…The wild herb Cistus incanus is not traditional in Bulgarian ethnomedicine but is widespread in all Strandja Mountain [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Content of biologically active compounds in the investigated extracts. * TPC expressed as the gallic acid equivalent which is commonly used in the pharmaceutical industry to determine the total phenol content 57 ; **TFC expressed as the quercetin equivalent. (2020) 10:6521 | https://doi.org/10.1038/s41598-020-63444-3…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, standardizing the processing parameters is of utmost importance. Domcheva et al [11] showed that the technique and conditions adopted for extraction process have a significant impact on the yield of polyphenols and flavonoids, as well as on the antioxidant capacity of the final product. In other study [12], the influence of plant parts and particle size of CI on the extractability of phenolic compounds was demonstrated.…”
Section: Carbonariusmentioning
confidence: 99%